Carbon Nanotube Anchored Organic Hydrogel for Soft Sensors. Issue 7 (11th May 2022) - Han, Libin; Qu, Rui; Chen, Dongsheng; Liu, Lei; Xu, Huidi; Zhang, Zhuanzhuan; Zhao, Yuze; Song, Xiaofeng
Abstract: Flexible hydrogel sensors are receiving increasing attentions due to their application in human–machine interaction. However, there are great challenges for developing hydrogel strain sensors such as the asymmetry among excellent mechanics properties, high conductivity, resistance to solvent volatilization, and frost resistance. An organic hydrogel is prepared by associating physicochemical driving process with binary medium. That is, acrylamide (AAm) and vinyl acetate (VAc) polymerize in the water/dimethyl sulfoxide (DMSO) solution of poly(vinyl alcohol) (PVA)/hydroxylated multi‐walled carbon nanotube (mCNT‐OH). The organic hydrogel sensor not only has good tensile strength, resistance to freezing, and solvent volatility, but also exhibits excellent strain sensitivity ( GF  = 6.39 in the range of 200–560%) due to the mCNT‐OH forming conductive pathway. Its response and recovery time are 80 and 60 ms, respectively. The strain sensitivity does not decline after 260 cyclic stretches at 200% strain. The organic hydrogel sensor can steadily trace large and subtle human motions. Then it is promising in the application of human–machine interface like aphasiac, physical exercise, or rehabilitation. Abstract : A CNT anchored organic hydrogel is developed by associating physicochemical driving processes with binary medium. It addresses the asymmetry among excellent mechanics properties, high conductivity, resistance to solvent volatilization and frost resistance, and can sensitively detect large and subtle motions.